'Break Down These Walls': Space, Relations, and Hierarchy in Fijian Evangelical Christianity. Issue 1 (March 2015) - Morgain, Rachel; Taylor, John P.; Morgain, Rachel
Abstract Patterns of sociality in Fijian evangelical Christianity differ from the mainline Fijian Methodist church in being notably less integrated with relations of vanua and chiefly hierarchy, leading scholars to speculate as to whether such traditions are more individualised. Analysing teachings, hymns, worship styles and spatial arrangements within a prominent Fijian Pentecostal ministry, I explore how sociality is produced through the interaction of spatial, conceptual, and embodied processes. Competing dynamics of hierarchy and equality, connections and boundaries, are mobilised within an overall framework that emphasises individual moral authority and personal relationship with God. Through this analysis, in conversation with previous studies, this paper argues for a critical examination of schemes of 'egalitarian individualism' and 'hierarchical holism', which, through the influence of Louis Dumont in particular, have been prominent in studies of Christianity and sociality in Oceania.